Functional Remodeling Associated With Language Recovery After Repetitive Transcranial Magnetic Stimulation in Chronic Aphasic Stroke - Lin, Bing-Fong; Yeh, Shih-Ching; Kao, Yu-Chieh Jill; Lu, Chia-Feng; Tsai, Po-Yi (Frontiers in Neurology, 2022)
Background Repetitive transcranial magnetic stimulation (rTMS) has shown promising efficacy in improving the language functions in poststroke aphasia. However, randomized controlled trials were lacking to investigate the rTMS-related neuroimaging changes underlying the therapeutic effects on language improvement in chronic aphasia. Objective In this study, we aimed to evaluate the effects of low-frequency rTMS (LF-rTMS) on chronic poststroke aphasia. We hypothesized that the deactivation of the right pars triangularis could restore the balance of interhemispheric inhibition and hence facilitated the functional remodeling of language networks in both hemispheres. Furthermore, the rTMS-induced functional reorganization should underpin the language recovery after rTMS. Methods A total of 33 patients (22 males; ages: 58.70±13.77 years) with chronic stroke in the left hemisphere and nonfluent aphasia were recruited in this randomized double-blinded study. The ratio of randomization between rTMS and sham group is 17:16. All patients received real 1-Hz rTMS or sham stimulation (placebo coil delivered <5% of magnetic output with similar audible click-on discharge) at the right posterior pars triangularis for 10 consecutive weekdays (stroke onset to the first stimulation: 10.97±10.35 months). Functional connectivity of language networks measured by resting-state fMRI was calculated and correlated to the scores of Concise Chinese Aphasia Test using the stepwise regression analysis. Results After LF-rTMS intervention, significant improvement in language functions in terms of comprehension and expression abilities were observed compared with the sham group. The rTMS group showed a significant decrease of coupling strength between right pars triangularis and pars opercularis with a strengthened connection between right pars orbitalis and angular gyrus. Furthermore, the LF-rTMS significantly enhanced the coupling strength associated with left Wernicke area. Results of regression analysis showed that the identified functional remodeling involving both hemispheres could support and predict the language recovery after LF-rTMS treatment. Conclusions We reported the therapeutic effects of LF-rTMS and corresponding functional remodeling in chronic poststroke aphasia. Our results provided neuroimage evidence reflecting the rebalance of interhemispheric inhibition induced by LF-rTMS which could facilitate future research in the refinement of rTMS protocol to optimize the neuromodulation efficacy and benefit the clinical management of stroke patients.